Practices and Perceptions of Audiologists in Addressing the Mental Health Needs of Older Adult Clients - Van Stelten, Carla (Department of Health and Rehabilitation Sciences, 2025)
Background: Mental disorders are prevalent in older adults. The most frequent mental disorders in older adults are depression and dementia, which have both been related to hearing loss. Audiologists, as hearing care professionals, may play an important role in early identification, referral, and management of these disorders. Small studies from high-income countries suggested that audiologists lack knowledge and skills related to addressing mental health needs. This study explored a broader spectrum of settings for audiologists' knowledge, practices, and perceptions regarding addressing mental health needs. Methodology: Explanatory sequential mixed methods design with a multi-national sample of audiologists. The first phase was a survey (n = 50) to obtain predominantly quantitative data. The second phase was online focus groups (n = 13) to obtain rich, qualitative data and enable triangulation. Results and Discussion: The majority of audiologists responded to mental health needs of their older adult clients and most believed that a better understanding of clients' psychosocial status would positively affect audiological care (86%; n = 43). Despite audiologists displaying knowledge of the impact of hearing loss on mental well-being, action related to the additional burden of hearing loss is not operationalised. Addressing psychosocial needs, including screening behaviours and referral destinations, lacked uniformity. Facilitators and barriers to providing mental health services in the audiological setting are described. Conclusions: Audiologists treat their clients holistically and recognise that clients' needs extend beyond their hearing loss. Knowledge enhancement and protocol development may help audiologists to address mental health needs in an evidence-based way.